2012
DOI: 10.1007/s11230-012-9355-x
|View full text |Cite
|
Sign up to set email alerts
|

Rhabdias esculentarum n. sp. (Nematoda: Rhabdiasidae) from green frogs of the Rana esculenta species complex in Italy: molecular evidence, morphological description and genetic differentiation from its congeners in frogs and toads

Abstract: A new taxon, Rhabdias esculentarum n. sp., is described based on DNA sequence analysis at multiple loci (i.e. mtDNA cox-1, 12S rRNA, ITS-1 and partial ITS-2 regions of the nuclear rDNA) and morphometric analysis carried out on specimens collected from the green frogs of the Rana esculenta species complex in Italy (i.e. R. lessonae Camerano and R. esculenta Linnaeus, identified genetically by diagnostic allozyme loci). Rhabdias esculentarum n. sp. was differentiated genetically, at both mitochondrial and nuclea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 42 publications
1
6
0
Order By: Relevance
“…Recent research suggests that specimens identified as R. bufonis represent a species complex (Tkach et al, 2014). Cipriani et al (2012) recently described R. esculentarum from both P. lessonae and P. esculentus in Italy, and our specimens in water frogs from HNP correspond to that species. We have not collected parasites from Bufo bufo (Linnaeus, 1758) or B. viridis, so we do not know if both R. bufonis and R. esculentarum do, or did, co-occur in the HNP.…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…Recent research suggests that specimens identified as R. bufonis represent a species complex (Tkach et al, 2014). Cipriani et al (2012) recently described R. esculentarum from both P. lessonae and P. esculentus in Italy, and our specimens in water frogs from HNP correspond to that species. We have not collected parasites from Bufo bufo (Linnaeus, 1758) or B. viridis, so we do not know if both R. bufonis and R. esculentarum do, or did, co-occur in the HNP.…”
Section: Discussionsupporting
confidence: 60%
“…The absence of C. retusus, C. ornata, G. cygnoides, H. asper, H. cylindracea, and P. loossi were confirmed by sampling in 2013. Murai et al (1983) did not report members of 2 common amphibian helminth taxa that we detected, including nematodes belonging to the genus Rhabdias, which includes species living in the lungs of both amphibians and some lizards (Cipriani et al, 2012;Kuzmin, 2013). Most studies of Rhabdias in European amphibians have reported R. bufonis, and Edelényi (1960) reported this worm from P. esculentus, P. ridibundus, and Bufo viridis near the HNP.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Molecular data have been successfully applied to the study of nematodes in general and, in particular, the genus Rhabdias (Cipriani, Mattiucci, Paoletti, Santoro, & Nascetti, ; Dare, Nadler, & Forbes, ; Dubey & Shine, ; Langford & Janovy, ; Lhermitte‐Vallarino et al, ; Morais et al, ; Nascimento et al, ; Tkach, Kuzmin, et al, ). Several molecular markers have been used for Rhabdiasidae, including ribosomal and mitochondrial genes (Cipriani et al, ; Dare et al, ; Dubey & Shine, ; Junker et al, ; Langford & Janovy, ; Lhermitte‐Vallarino et al, ; Nascimento et al, ; Tkach, Halajian, & Kuzmin, ; Tkach, Kuzmin, et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the molecular studies conducted for this genus, some used DNA sequences only to distinguish closely related species (Cipriani et al, ; Junker et al, ; Lhermitte‐Vallarino et al, ) although others reported on a broader taxon sampling, improving the phylogenetic reconstruction (Dare et al, ; Dubey & Shine, ; Langford & Janovy, ; Tkach, Halajian, et al, ; Tkach, Kuzmin, et al, ). Using morphological and molecular data, Tkach, Kuzmin, et al, added considerable information on the taxonomy of Rhabdiasidae studying a broad phylogeny with species from several continents, in which a new genus ( Serpentirhabdias ) was proposed, together with notes on its biology, morphology, geographical distribution and host–parasite relationships.…”
Section: Introductionmentioning
confidence: 99%